2013
DOI: 10.1007/s10103-013-1276-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 830-nm diode laser irradiation on human sperm motility

Abstract: Sperm motility is known as an effective parameter in male fertility, and it depends on energy consumption. Low-level laser irradiation could increase energy supply to the cell by producing adenosine triphosphate. The purpose of this study is to evaluate how the low-level laser irradiation affects the human sperm motility. Fresh human semen specimens of asthenospermic patients were divided into four equal portions and irradiated by 830-nm GaAlAs laser irradiation with varying doses as: 0 (control), 4, 6 and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 28 publications
4
10
0
1
Order By: Relevance
“…Interestingly, our data suggest that the effects of exposing horse spermatozoa to red-light heavily rely upon the specific utilized light-dark interval. These findings are similar to those observed in previous studies based on the use of both laser and LED-based light sources in species such as dogs [ 17 ], buffalos [ 34 ], and humans [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, our data suggest that the effects of exposing horse spermatozoa to red-light heavily rely upon the specific utilized light-dark interval. These findings are similar to those observed in previous studies based on the use of both laser and LED-based light sources in species such as dogs [ 17 ], buffalos [ 34 ], and humans [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, these data also suggest that low levels of irradiation have greater but variable effect on tissues than higher levels of irradiation. This variable response, including the impact upon sperm motility, has already been described elsewhere [ 12 , 13 , 35 , 37 , 40 , 41 ] although one study with human sperm suggested a linear relationship between the dose of red-light irradiation and sperm motility [ 42 ]. However, taking into account the considerable difference in the response to light between species, a more in-depth study is needed to establish better the mechanisms underlying the observed variability.…”
Section: Discussionmentioning
confidence: 67%
“…This improvement was associated with an increase in peroxynitrite production in the photostimulated spermatozoa without affecting sperm viability. Similar results with respect to motility have been reported in human, buffalo and turkey spermatozoa exposed to different laser irradiation systems (Abdel‐Salam et al, ; Iaffaldano et al, ; Salman Yazdi et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…These data clearly point out that the improving effect on boar sperm function induced by red LED-based light depends on the photo-stimulation pattern. A similar phenomenon has been described when laser systems are applied to sperm from other mammalian species like dog, buffalo and human 25 32 33 . Therefore, it seems that light-effects on mammalian sperm rely on precise rhythms and rates of application, regardless of light source and wavelength range.…”
Section: Discussionsupporting
confidence: 66%